If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(z + 3) = -6z Reorder the terms: -5(3 + z) = -6z (3 * -5 + z * -5) = -6z (-15 + -5z) = -6z Solving -15 + -5z = -6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6z' to each side of the equation. -15 + -5z + 6z = -6z + 6z Combine like terms: -5z + 6z = 1z -15 + 1z = -6z + 6z Combine like terms: -6z + 6z = 0 -15 + 1z = 0 Add '15' to each side of the equation. -15 + 15 + 1z = 0 + 15 Combine like terms: -15 + 15 = 0 0 + 1z = 0 + 15 1z = 0 + 15 Combine like terms: 0 + 15 = 15 1z = 15 Divide each side by '1'. z = 15 Simplifying z = 15
| (4x^2+3)(2x-3)=0 | | 9=8h | | 9x+8+4x+6= | | -9b-3=3(b+2) | | N-2.6+11.44=-3.53n-21.964 | | 5x-16x= | | 0=4x^2-8x+2 | | 6x+24=3x-15 | | -(6y+1)-(-5y-4)=1 | | 7z-3=1+9z | | 28+24m=35+17m | | -3(7p+4)+-2(5+17p)+-3(4+4p)=0 | | 5y-6=6y-4 | | -7=q-7 | | 0=x^2+4x+9 | | 3m-24=45+6m | | 4(5x-3)+2(10-2x)=5(3x+2)-5 | | 1/5(x+9)=6 | | 11x+x= | | 3x+7x*7x-8x+6x*6x= | | 45(x+5)=0 | | 12a=b | | -3(7p+4)-2(5-17p)-3(4+4p)=0 | | 1=2x+0.5 | | 5(7c-1)-10=33c+5 | | 0=x^2-2x-7 | | -(9-6a)-(6+5a)-26=-(4-7a)+(-a)+3 | | a^2+4*a=45 | | 3(1-3b)=-6b+15 | | -3y-6y= | | 66-y=58 | | -5n+8=4m |